Pengaruh Artificial Intelligence Berbasis Wordwall Dalam Pembelajaran Pendidikan Agama Kristen Terhadap Keaktifan Belajar Siswa - Immanuel Damayanto Nugroho; Aprilius Nahak; Moralman Gulo; Indah Kariawati Gulo; Krisbianto Anes (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2026)
This research is motivated by the low level of student learning engagement, which remains a challenge in education. In class, students often tend to be passive, reluctant to ask questions, and less involved in discussions, resulting in less interactive learning. This study aims to determine the effect of Wordwall-based AI on student learning engagement and to determine the extent of this influence. The method used was quantitative research with a correlational approach. Data were analyzed using the coefficient of determination test. The results showed an R-square value of 0.394, indicating that the use of Wordwall contributed 39.4% to student learning engagement. Meanwhile, 60.6% was influenced by factors outside the research variables. Therefore, the use of Wordwall-based AI can be an alternative learning medium to increase student learning engagement.